Synthesis ,Characterization and invitro evaluation of anticancer activity of new hydroxamicacid basedHDACi containing substituted thaizolesas a cap linking moiety. - Hamed, Fadil M .; Mohammad, Mohammad .H. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The present study was undertaken to synthesize, characterize and evaluate the anticancer activity of new derivatives of hydroxamate –based HDACi having S-subistituted-5-amino1,3,4thadiazole as a cap linking moiety ,with suitable aliphatic linker.The structures and purity of the targeted compounds were confirmed by TLC , FTIR ,H-NMR and mass spectroscopy and their anticancer activity were evaluated by comparative cytotoxic study , Using HeLa nuclear extract and normal embryonic fibroblasts cell lines.All the synthesized compounds shows good anticancer activity, represented by their high rate of growth inhibition on Hela cell line and low cytotocic effect on normal cell line .Compound (VAb) show the best safety index(SI) that represented by its selective cytotoxic activity on HeLa cell linewith low cytotoxic effect on normal embryonic cell line.